A Review of General Practice System Certification Programs in Seven Countries and Five Canadian Provinces - Dave A. Ludwick and John Doucette (ElectronicHealthcare, 2009)
Introduction: Health information technology can improve quality of care, reduce medical errors and increase health system efficiency. Certification programs facilitate adoption by regulating the general practice (GP) systems market against functionality and interoperability standards, thereby reducing liability risk due to functional deficiency. Purpose: In a previous international literature review, certifications claimed to facilitate procurement and mitigate financial, procurement and liability risk. The purpose of this review was to assess the effectiveness of certification programs in driving the adoption of GP systems. Methods: We completed a literature review of English-language, peer-reviewed and grey literature, government and organizational Websites, as well as trade press, general press, and online sources published from January 1, 2005 to October 2008. We qualified these findings by consulting key informants. Results: Four databases, 11 journal websites, 15 websites from grey sources, 10 medical college and professional association websites and 21 government/commission websites were searched. The searches returned 2705 article titles. Fifty-one unique articles met our inclusion and exclusion criteria. Certification organizations were found in Alberta, British Columbia, Saskatchewan, Manitoba, Ontario, the UK, the USA, Denmark, Australia and New Zealand. Conclusions: Certification organizations manage evaluation, procurement, financial, technical and software maintenance risk for GPs. They offer funding and support to qualified physicians who adopt an approved GP system. Reimbursement may be contingent upon integration with a jurisdictional infostructure, reporting usage of systems or achieving quality of care benchmarks. We recommend that certification organizations include payer and physician representation. Certification organizations are advised to limit the number of approved systems to a range of three to six systems. Organizations are encouraged to tie physician reimbursement for systems adoption to usage or, better still, to reporting quality of health outcomes. Jurisdictions should control the frequency of systems upgrades by using a release management process that mitigates risks pertaining to software operations.
Keywords: GP systems, electronic medical records, electronic health records, ambulatory care system, practice management system, physician office system, reimbursement, interoperability, certification, accreditation, regulation, approval, conformance, risk mitigation, procurement, liability